Galanin: a hypothalamic-hypophysiotropic hormone modulating reproductive functions. - López, F J (1991)
Galanin (GAL) is widely distributed in the peripheral and the central nervous systems. In the brain, the highest GAL concentrations are observed within the hypothalamus and, particularly, in nerve terminals of the median eminence. This location, as well as GAL actions on prolactin, growth hormone, luteinizing hormone (LH), and LH-releasing hormone (LHRH) secretion, suggest the possibility that GAL may act as a putative hypothalamic-hypophysiotropic hormone. To establish this, GAL and LHRH levels were measured in hypophyseal portal plasma samples using specific radioimmunoassays. Rat galanin (rGAL) concentrations in portal blood were approximately 7-fold higher than those observed in peripheral plasma in male and female (estrus, diestrus) rats, indicating an active secretory process of rGAL into the portal vasculature. Frequent (10 min) sampling revealed that rGAL and LHRH were secreted into the portal circulation in a pulsatile manner with a pulse frequency of one pulse per hour. Interestingly, both hormone series depicted a high degree of coincident episodes. In fact, the probability of random coincidence, calculated by the algorithm HYPERGEO, was less than 0.01. Moreover, the retrograde tracer Fluoro-Gold, when given systemically, was taken up by GAL neurons in the hypothalamus, including a subset of neurons expressing rGAL and LHRH, strengthening the notion of the existence of a GAL neuronal system connected to the hypophyseal portal circulation. These observations reinforce the concept that GAL regulates pituitary hormone secretion. To analyze this in further detail, the effects of rGAL on LH secretion were evaluated under basal and stimulated conditions. rGAL induced a small but dose-dependent increase in LH secretion from cultured, dispersed pituitary cells. Interestingly, rGAL enhanced the ability of LHRH to stimulate LH release. The tight link between GAL and LHRH neuronal systems is strengthened by the observation that during the estrous cycle of the rat, rGAL and LHRH contents in the median eminence show an identical profile (r = 1.00). These data indicate that GAL should be considered as a hypothalamic-hypophysiotropic hormone and as an important neuromodulator of LHRH secretion and action. The colocalization and cosecretion of GAL and LHRH and the cooperative action at the level of the anterior pituitary afford important evidence for the functional significance of coexistence of neurotransmitters in neurons of the central nervous system.